The value of cardiac magnetic resonance imaging in endocardial fibroelastosis - Xiao, Wenjiao; Wang, Yuanlin; Cheng, Weiqin; Zhang, Yuting (Frontiers in Pediatrics, 2022)
Introduction: Endocardial fibroelastosis (EFE) is an uncommon cardiomyopathy often occurring in infants with a poor prognosis. It is of great significance to make an early diagnosis and accurate cardiac function analysis for clinical treatment and prognosis. This study aims to explore the findings of cardiac magnetic resonance (CMR) in patients with EFE, including morphological changes and cardiac function analysis. Additionally, we compare the difference in the evaluation of the cardiac function between CMR and Echocardiography (Echo). Methods and Patients: 11 patients with EFE (9 females and 2 males, aged 0.3-1.9 years) treated in our hospital were retrospective analyzed. All patients underwent CMR and Echo within 2 weeks after being admitted to hospital. The cardiac function indexes measured with both CMR and Echo included left ventricular end-diastolic volume (EDV), end-systolic volume (ESV), ejection fraction (EF), fractional shortening (FS), Left ventricular anterior wall thickness (LVAW) and posterior wall thickness (LVPW), etc. Cardiac function of the patients was graded according to the New York Heart Association functional classification. The imaging data obtained from MRI or Echo were correlated with the clinical cardiac function classification. Results: All patients showed obviously thickened endocardium and left ventricle globular dilatation on CMR. Significant systolic dysfunction and segmental or whole abnormal ventricular movement was observed. The values of EF, FS and EDV were significantly lower in CMR measurements than in Echo measurements. The values of ESV, ESD, LVAW and LVPW were significantly higher in CMR measurements than in Echo measurements. EF and FS measured with CMR had a better correlation with the clinical cardiac functional score than Echo (r=0.597 and r=0.430；r=0.224 and r=0.245, respectively). Conclusion: CMR could accurately display the characteristic morphological changes of the heart in patients with EFE. The parameters measured by CMR are more accurate than echo and have good correlation with clinical cardiac functional score, mainly because it does not make invalid geometrical assumptions.